2021
DOI: 10.3390/polym13203588
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Wear Behaviour of Coated Polymer Gears

Abstract: A comprehensive experimental investigation of the wear behaviour of coated spur polymer gears made of POM is performed in this study. The three physical vapour deposition (PVD) coatings investigated were aluminium (Al), chromium (Cr), and chromium nitrite (CrN). Al was deposited in three process steps: By plasma activation, metallisation of Al by the magnetron sputtering process, and by plasma polymerisation. Cr deposition was performed in only one step, namely, the metallization of Cr by the magnetron sputter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…of the analysed polymeric component. As already presented by the authors of this paper [ 1 ], the influence of very thin PVD-coatings (less than 500 nm) on the wear behaviour of POM polymer spur gears is small and does not reduce the wear significantly. For that reason, the multilayer (thicker) PVD-coatings made of Al, Cr, and CrN should be considered in the future.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…of the analysed polymeric component. As already presented by the authors of this paper [ 1 ], the influence of very thin PVD-coatings (less than 500 nm) on the wear behaviour of POM polymer spur gears is small and does not reduce the wear significantly. For that reason, the multilayer (thicker) PVD-coatings made of Al, Cr, and CrN should be considered in the future.…”
Section: Introductionsupporting
confidence: 60%
“…Polymer gears are used widely in many engineering applications, such as office appliances, mechatronic devices, household facilities, and medical instruments [ 1 , 2 , 3 ]. They can operate without lubrication and, therefore, may be used in some typical applications where lubrication is not desired (household appliances, the food industry, medicine, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer gears can be produced by classical cutting processes or, for large series production, by injection moulding [12]. Injection moulding is a specific gear production process that results in distinct types of gear geometry deformations [13]. If the process parameters are unsuitable, these deformations can be very substantial and can seriously influence the polymer gear's service life.…”
Section: Introductionmentioning
confidence: 99%
“…In the authors’ previous work [ 52 ], we analysed the fatigue behaviour of coated spur polymer gears, where only one coating layer was investigated, made of aluminium (Al), chromium (Cr), or chromium nitride (CrN). The experimental results showed that the influence of Al, Cr, or CrN surface coatings on the wear behaviour of the analysed polymer gear was not significant.…”
Section: Introductionmentioning
confidence: 99%